Prevalence and risk factors of diabetic nephropathy among type 2 diabetes patients in family medicine clinic AFHSR Khamis Mushait - Saeed Mohammed Al-Shahrani; Bandar Mohammed Shaher; Yahya Mohammed Alragea; Fatima Mohammad Ali Alqahtani; Amjad Saeed Mansour Binghamiah; Mansour Ali Mansour Alqahtani; Saad Abdullah Mufrrih (Journal of Family Medicine and Primary Care)
Background: Diabetic nephropathy is a frequent complication of diabetes mellitus, affecting a considerable proportion of patients. Despite confirmed rising prevalence worldwide, little is known about its epidemiology in Saudi Arabia or its connection to glycemic or lipid parameters. Methods: This was a cross-sectional questionnaire-based observational study. We modeled the data using mixed effects logistic regression modeling. Results: Our sample was constituted of (n = 415) type 2 diabetes patients. The prevalence for diabetic nephropathy was [n = 17, 4.1% (95% confidence interval, CI: 3.7% to 4.4%)]. Unadjusted risk factors were older age profile, comorbid diabetic retinopathy, comorbid stroke, lower BMI, and injecting insulin. However, tobacco smoking, neuropathy, family history of diabetes, or renal disease did not bear any significant association with diabetes nephropathy among our participants. Risk factors related to glycemic and lipid profiles included initial FBG levels and HbA1c percentages and initial and later cholesterol and LDL levels. Initial and later HDL levels were protective from diabetic nephropathy. At the adjusted analysis, only the number of children (HR = 0.3151, P = 0.02256) and triglyceride levels were associated with higher diabetic nephropathy risk (HR = 3.1709, P = 0.03218). Conclusion: Our estimate for diabetic nephropathy prevalence is exceedingly low compared to global figures. This may be related to impaired identification of diabetic nephropathy in Saudi Arabia. Our survey is the first in Saudi Arabia to confirm a link between reduced fertility and diabetic nephropathy. Our study, also, uniquely identifies a strong link between hypertriglyceridemia and diabetic nephropathy among Saudi patients.